Technology blueprint: YUQY Electronic Sdn Bhd / Luqman Afiq Mohd Adnan - Mohd Adnan, Luqman Afiq (2020)
Our company produces the vacuum cleaner that we call it as Vaclower with an innovation by combining dry/wet vacuum cleaner with a blower. The design and style of our product is unique. We offer superior quality and design at affordable prices. Our products, design and finishes will continue evolving based on consumer trends and demands